1988
DOI: 10.2190/9p69-xcur-c3na-2dck
|View full text |Cite
|
Sign up to set email alerts
|

The Artist and Androgyny: A Study of Gender Identity in Visual Artists

Abstract: While art is an activity that is socially valued, the image of the artist as perceived by the public and expressed in the literature has rarely been studied empirically. The Adjective Check List is used to test one dimension of this issue-June Wayne's hypothesis that the artist is a stereotypical woman, focusing on the artist's view of himself/herself and artists in general. Data were gathered by means of a questionnaire mailed to 1753 artists who had been nominated for the national Awards in Visual Arts durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…As all the paintings were executed by women, had such a female aesthetic existed, the general mean score should have been much higher, skewed to the "femiaine" side of the index. The findings of this study seem to concur with the conclusions of Harris, Smith and Perricone (1988) that in their creative work artists are androgynous instead of being stereotypically "male-or "female." This also agrees with Birg and Peterson (1985):…”
Section: Ga-femalesupporting
confidence: 87%
“…As all the paintings were executed by women, had such a female aesthetic existed, the general mean score should have been much higher, skewed to the "femiaine" side of the index. The findings of this study seem to concur with the conclusions of Harris, Smith and Perricone (1988) that in their creative work artists are androgynous instead of being stereotypically "male-or "female." This also agrees with Birg and Peterson (1985):…”
Section: Ga-femalesupporting
confidence: 87%
“…Possibly related to this hypothesized greater psychological conflict, there is support for a relationship between creativity and androgeny. Male and female visual artists were found to possess androgenous gender identities (Harris et al, 1988), and creative architects were found to score higher than non-creatives on a measure of androgeny (MacKinnon, 1962), although Bem (1974) failed to find such a relation for creative women.…”
Section: Introductionmentioning
confidence: 99%